The alpha and beta chains of avian retrovirus reverse transcriptase independently expressed in Escherichia coli: characterization of enzymatic activities. - Soltis, D A (1988)
Reverse transcriptase of the avian sarcoma and leukosis retroviruses is a heterodimer composed of a 63-kDa alpha and a 95-kDa beta polypeptide chain, both of which are encoded in the pol gene and are produced by proteolytic processing of a larger precursor. We previously constructed a bacterial expression clone of the entire pol coding region that produces a protein 4 kDa larger than the mature viral beta subunit. By use of this clone and synthetic oligonucleotides to introduce stop codons, two derivatives have been constructed: one that directs synthesis of a protein equivalent to the mature beta subunit and the other that directs synthesis of a protein equivalent to alpha subunit. Predicted amino acid sequences of these proteins differ from their viral counterparts only by an initiator methionine that was added to the N termini for expression in Escherichia coli. Both bacterially expressed proteins exhibit reverse transcriptase activity and appear to function as homodimers. The properties of these proteins resemble those of the viral reverse transcriptase heterodimer; however, the bacterially produced alpha dimer protein could be distinguished from the other proteins by its increased sensitivity to heat inactivation, which also has been reported for the corresponding viral product. These results show that correct folding and expression of enzymatic function does not require formation of a precursor. The alpha and beta clones provide a convenient source of individual pol gene products for further evaluation of their roles in the synthesis and integration of retroviral DNA.